Local resource mobilization for malaria vector control among Rwandan rice farmers: a pilot study into the role of community ownership - Alexis Rulisa; Luuk van Kempen; Emmanuel Hakizimana; Constantianus J. M. Koenraadt (BMC, 2023)
Abstract Background Evidence suggests a vicious cycle between rice cultivation and malaria control in Rwanda. Rice fields offer an attractive breeding ground for malaria vectors, which increases the disease burden in rice farming communities, and, consequently, reduces productivity in the rice sector. Community-based larval source management in rice fields is propagated as a sustainable solution to break this cycle. A sense of agency and ownership of malaria control interventions, as well as the mobilization of resources at the local level, are often considered preconditions for success. However, an evidence gap exists regarding the interaction between the agentive and financial dimension of local sustainability. Methods We conduct a larviciding pilot involving three groups; one group where rice farmers sprayed their fields under expert supervision, one group where rice farmers organised the larviciding campaign themselves, and a (non-sprayed) control group. We test whether the difference in agency between the intervention groups affects farmers' willingness-to-pay for a larviciding campaign. Willingness-to-pay is elicited in a contingent valuation exercise, more specifically a bidding game, and is assessed both before and after the pilot (n = 288). Difference-in-difference estimates are computed, using a propensity score matching technique. Supplementary data were collected in a survey and two focus group discussions for triangulation. Results The high-agency (self-organised) group significantly outperforms the low-agency (expert-supervised) group in terms of maintaining its willingness to contribute financially. However, higher willingness-to-pay in the high-agency group does not appear to be driven by a stronger sense of ownership per se. The supplementary data indicate high levels of ownership in both treatment groups compared to the control group. A tentative explanation lies in diverging perceptions concerning the effectiveness of the pilot. Conclusions The study supports the idea that community-led organization of larval source management can prove instrumental in mobilizing finance for malaria control in low-income settings where rice production interferes with the fight against malaria. However, the causality is complex. Feelings of ownership do not appear the main driver of willingness-to-pay, at least not directly, which opens up the possibility of initiating community-driven malaria control interventions that promote the agentive and financial dimension of local sustainability simultaneously.